SARS-CoV-2 detection by targeting four loci of viral genome using graphene oxide and gold nanoparticle DNA biosensor - Arman Amani Babadi; Shahrooz Rahmati; Rafieh Fakhlaei; Reza Heidari; Saeid Baradaran; Mostafa Akbariqomi; Shuang Wang; Gholamreza Tavoosidana; William Doherty; Kostya Ostrikov (Scientific Reports, 2022)
Abstract The current COVID-19 pandemic outbreak poses a serious threat to public health, demonstrating the critical need for the development of effective and reproducible detection tests. Since the RT-qPCR primers are highly specific and can only be designed based on the known sequence, mutation sensitivity is its limitation. Moreover, the mutations in the severe acute respiratory syndrome β-coronavirus (SARS-CoV-2) genome led to new highly transmissible variants such as Delta and Omicron variants. In the case of mutation, RT-qPCR primers cannot recognize and attach to the target sequence. This research presents an accurate dual-platform DNA biosensor based on the colorimetric assay of gold nanoparticles and the surface-enhanced Raman scattering (SERS) technique. It simultaneously targets four different regions of the viral genome for detection of SARS-CoV-2 and its new variants prior to any sequencing. Hence, in the case of mutation in one of the target sequences, the other three probes could detect the SARS-CoV-2 genome. The method is based on visible biosensor color shift and a locally enhanced electromagnetic field and significantly amplified SERS signal due to the proximity of Sulfo-Cyanine 3 (Cy3) and AuNPs intensity peak at 1468 cm-1. The dual-platform DNA/GO/AuNP biosensor exhibits high sensitivity toward the viral genome with a LOD of 0.16 ng/µL. This is a safe point-of-care, naked-eye, equipment-free, and rapid (10 min) detection biosensor for diagnosing COVID-19 cases at home using a nasopharyngeal sample.